Investigating Death Anxiety, Resilience, and Job Burnout Among Prehospital Emergency Personnel: A Multicenter Cross‐Sectional Study in Iran - Ali Ghahramanipirsalami; Farzaneh Modaresi; Parisa Sabetsarvestani; Azizallah Dehghan; Saeed Abedi; Mostafa Bijani (Health Science Reports)
ABSTRACT Background and Aims As first responders to accidents and disasters, prehospital emergency personnel encounter psychological crises and mental stressors like death anxiety and job burnout. The present study aimed to investigate death anxiety, resilience, and job burnout in prehospital emergency personnel. Methods This investigation employed a descriptive, cross‐sectional, observational, and multi‐centric study design. The research population encompassed prehospital emergency personnel affiliated with three universities of medical sciences in Fars Province, Southern Iran. A convenience sampling technique yielded a participant pool of 417 prehospital emergency personnel. Data was gathered using the Templer Death Anxiety Scale, Prehospital Emergency Personnel Resilience Scale and Maslach Burnout Inventory. Data were analyzed in SPSS‐26 through descriptive statistics, one‐way ANOVA, Pearson coefficient, and multiple linear regression. The significance level was set at p < 0.05. Results The mean score for job burnout was 61.36 (SD ± 36.76), while the mean score for death anxiety was 99.5 (SD ± 94.10). These scores can be interpreted as indicative of high levels of both job burnout and death anxiety. Conversely, the mean resilience score of 96.37 (SD ± 77.06) suggests moderate resilience within the sample population. The findings revealed an inverse correlation between resilience and job burnout (r = −0.49, p < 0.001) and an inverse correlation between resilience and death anxiety (r = −0.51 p < 0.001). Also, the findings revealed a statistically significant positive correlation was found between job burnout and death anxiety (r = 0.37, p < 0.001). The results showed that age, work experience, resilience, and job burnout explained 44.4% of the variance in death anxiety (R2 = 0.44, p < 0.001). In addition, work experience (β = 0.097, p = 0.043), resilience (β = 0. 208 p < 0.001), and job burnout (β = 0.337, p < 0.001) had the highest predictive impact on death anxiety. Conclusion While the present study revealed high levels of death anxiety and job burnout among prehospital personnel, it also found their resilience to be moderate. Senior managers in prehospital emergency services should prioritize strategies to improve cognitive abilities, particularly resilience. By doing so, they can not only enhance employee well‐being but also potentially reduce job burnout and death anxiety.